A rare complication in management of traumatic optic neuropathy - Sushad Prasad; Priya Sivakumar (Kerala Journal of Ophthalmology)
Traumatic head injury can cause inappropriately increased Antidiuretic hormone (ADH) secretion, causing water retention and thereby dilutional hyponatremia. Corticosteroids despite controversies, form an important line in the management of traumatic optic neuropathy (TON). Treatment with steroids in patients with undiagnosed Syndrome of Inappropriate ADH Secretion (SIADH) can cause life-threatening hyponatremias. The patient diagnosed with right eye TON was treated with systemic steroids. She developed fatigability, vomiting, and pedal edema. Electrolyte profile and urinary sodium showed hyponatremia and natriuresis following which SIADH was diagnosed. Steroids were stopped; the Patient was started on hypertonic saline, a salt-restricted diet, and Tolvapatan after which sodium levels normalized. Electrolyte workup has a major role in TON management with steroids.